2006
DOI: 10.1073/pnas.0509952103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the mobile light-harvesting complex II polypeptides for state transitions in Chlamydomonas reinhardtii

Abstract: State transition in photosynthesis is a short-term balancing mechanism of energy distribution between photosystem I (PSI) and photosystem II (PSII). When PSII is preferentially excited (state 2), a pool of mobile light-harvesting complex II (LHCII) antenna proteins is thought to migrate from PSII to PSI, but biochemical evidence for a physical association between LHCII proteins and PSI in state 2 is weak. Here, using the green alga Chlamydomonas reinhardtii, which has a high capacity for state transitions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 43 publications
(51 reference statements)
13
195
4
1
Order By: Relevance
“…Notably, LHCBM1, LHCBM3, LHCBM4/6, and LHCBM2/7, which are part of trimeric LHCII complexes (Stauber et al, 2003), were found to be decreased between 3.5-and 2-fold, where LHCBM1 was most affected, with 3.5-fold reduction in the ami-RNApsbr-2 strain. In contrast, LHCBM5, involved in state transitions in C. reinhardtii (Takahashi et al, 2006), appeared to be unchanged.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of mentioning
confidence: 82%
“…Notably, LHCBM1, LHCBM3, LHCBM4/6, and LHCBM2/7, which are part of trimeric LHCII complexes (Stauber et al, 2003), were found to be decreased between 3.5-and 2-fold, where LHCBM1 was most affected, with 3.5-fold reduction in the ami-RNApsbr-2 strain. In contrast, LHCBM5, involved in state transitions in C. reinhardtii (Takahashi et al, 2006), appeared to be unchanged.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of mentioning
confidence: 82%
“…In complex I-deficient cells, we found that two protein spots corresponding to LHCII proteins Lhcb5/CP26 and Lhcbm2 were less abundant than in wild type but this was not paralleled with a change in other LHCII protein amounts, PSII-LHCII amount, or PSII absorption cross section. Both proteins play a critical role in state transition process and Lhcb5/CP26 is phosphorylated upon state transition (Ferrante et al, 2012;Takahashi et al, 2006). This might indicate that the decrease in Lhcb5 protein observed in complex I mutant is due a slight difference in the ratio between non-phosphorylated/phosphorylated Lhcb5/CP26 protein.…”
Section: Discussionmentioning
confidence: 99%
“…This gives rise to an asymmetric conformation of the complex, as all 4 LHCI subunits are located in one side of the complex. The opposite side is occupied by PsaL and PsaH, of which, PsaH has been suggested to serve as a docking site for mobile LHCII possibly migrated from PSII upon state-transitions (Takahashi et al, 2006;Amunts et al, 2007). This subunit is not present in cyanobacterial as well as red algal PSI, since the antennae of PSII in both organisms are membrane-peripheral phycobilisomes instead of LHCII.…”
Section: Photosystem Imentioning
confidence: 99%